Serial hemodynamic monitoring to guide treatment of maternal hypertension leads to reduction in severe hypertension. (5th January 2017) - Stott, D.; Papastefanou, I.; Paraschiv, D.; Clark, K.; Kametas, N. A.
Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points. ABSTRACT: Objectives: To examine whether treatment for hypertension in pregnancy that is guided by serial monitoring of maternal central hemodynamics leads to a reduction in the rate of severe hypertension, defined as blood pressure ≥ 160/110 mmHg; and to assess the distinct longitudinal hemodynamic profiles associated with beta‐blocker monotherapy, vasodilator monotherapy and dual agent therapy, and their relationships with outcomes, including fetal growth restriction. Methods: This was a prospective observational study at a dedicated antenatal hypertension clinic in a tertiary UK hospital. Fifty‐two untreated women presenting with hypertension were recruited consecutively and started on treatment, either with a beta‐blocker or a vasodilator. The choice of initial antihypertensive agent was determined according to a model constructed previously to predict the response to the beta‐blocker labetalol in pregnant women needing antihypertensive treatment. At presentation, the demographic and maternal hemodynamic variables associated with a therapeutic response to labetalol, defined as blood pressure control < 140/90 mmHg with labetalol monotherapy throughout pregnancy, were ascertained and analyzed with logistic regression to create a model to predict sustained blood pressure control as described above. The women were reviewed regularly until delivery and underwent serial hemodynamic monitoring throughout pregnancy. If their blood pressure was elevated, the prediction model was referred to again to determine if alternative antihypertensive therapy, either with additional beta‐blocker or a vasodilator, should be added. Results: Treatment by referring to results of serial hemodynamic monitoring reduced the rate of severe antenatal hypertension from 18% to 3.8%. Seventy‐seven percent of women were initially prescribed a beta‐blocker and 23% a vasodilator. The group that maintained good blood pressure control with beta‐blocker monotherapy had the best fetal and maternal outcomes. They had lower blood pressures at presentation and throughout gestation, demonstrated well‐maintained cardiac output and had the lowest rates of fetal growth restriction. The groups that required dual therapy to control their blood pressure had persistently higher blood pressure and rate of fetal growth restriction. The groups that required vasodilator therapy due to high levels of peripheral vascular resistance, either at presentation or later in pregnancy, accounted for 81% of cases with fetal growth restriction. Conclusion: Using serial hemodynamic monitoring in pregnancy to guide treatment of hypertension significantly reduces the rate of severe hypertension and allows identification of high‐resistance, low‐output hypertensive pregnancies that are associated with an increased rate of fetal growth restriction. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. RESUMEN Objetivos: Examinar si el tratamiento para la hipertensión en el embarazo guiado por un seguimiento en serie de las principales constantes hemodinámicas de la madre conduce a una reducción en la tasa de hipertensión grave, definida como presión arterial ≥ 160/110 mmHg; y evaluar los diferentes perfiles hemodinámicos longitudinales asociados a la monoterapia con beta‐bloqueantes, la monoterapia con vasodilatadores y la terapia dual, y su relación con los resultados, como la restricción del crecimiento fetal. Métodos: Se realizó un estudio observacional prospectivo en una clínica especializada en hipertensión prenatal de un hospital de atención terciaria del Reino Unido. Se reclutaron consecutivamente a cincuenta y dos mujeres no tratadas que presentaban hipertensión y se comenzó a tratarlas, bien con un beta‐bloqueante o bien con un vasodilatador. La elección del agente antihipertensivo inicial se determinó de acuerdo con un modelo elaborado previamente para predecir la respuesta al beta‐bloqueante labetalol en mujeres embarazadas que necesitaban tratamiento antihipertensivo. Al inicio se registraron las características demográficas y las variables hemodinámicas maternas asociadas con una respuesta terapéutica al labetalol, definida como un control de la presión arterial < 140/90 mmHg con monoterapia de labetalol durante todo el embarazo que se analizó mediante regresión logística para crear un modelo con el que pronosticar un control sostenido de la presión arterial, como se describe arriba. Las mujeres fueron sometidas a revisiones regulares hasta el momento del parto y se les hizo un seguimiento hemodinámico en serie durante todo el embarazo. Si la presión arterial era elevada, se empleó de nuevo el modelo de predicción para determinar si se debería añadir un tratamiento antihipertensivo alternativo, ya sea con un beta‐bloqueante adicional o con un vasodilatador. Resultados: El tratamiento que tuvo en cuenta los resultados del seguimiento hemodinámico en serie redujo la tasa de hipertensión prenatal grave del 18% al 3, 8%. Al 77% de las mujeres se les recetó inicialmente un y al 23% un vasodilatador. El grupo que mantuvo un buen control de la presión arterial con monoterapia de beta‐bloqueantes logró mejores resultados fetales y maternos. Este grupo tuvo menor presión arterial al inicio y durante toda la gestación, mostró un gasto cardíaco en buen estado y tuvo las tasas más bajas de restricción del crecimiento fetal. Los grupos que requirieron terapia dual para controlar su presión arterial mostraron persistentemente una mayor presión arterial y un mayor ritmo de restricción del crecimiento fetal. Los grupos que requirieron tratamiento vasodilatador debido a los altos niveles de resistencia vascular periférica, tanto al inicio como durante el embarazo, representaron el 81% de los casos con restricción del crecimiento fetal. Conclusión: El uso de un seguimiento hemodinámico en serie en el embarazo como guía para el tratamiento de la hipertensión reduce significativamente la tasa de hipertensión severa y permite la identificación de embarazos con hipertensión de alta resistencia y malos resultados, asociados con una mayor tasa de restricción del crecimiento fetal. 目的 : 探讨通过连续监测孕妇中心血流动力学改变指导妊娠期高血压的治疗能否降低重度高血压(血压≥ 160/110 mmHg)的发生率;评估β受体阻滞剂单药治疗、血管扩张剂单药治疗以及两种药物联合治疗时不同的纵向血流动力学情况, 以及其与妊娠结局(包括胎儿生长受限)的关系。 方法 : 本研究是在英国一家三级医院的产前高血压专科门诊进行的前瞻性观察性研究。连续纳入52例未接受过治疗、因高血压就诊的孕妇, 选择β受体阻滞剂或血管扩张剂作为最初用药。最初的抗高血压药物的选择是根据之前建立用于预测需要接受抗高血压治疗的孕妇对β受体阻滞剂拉贝洛尔的应答情况的模型。就诊时, 确定与拉贝洛尔治疗应答(即整个妊娠期间拉贝洛尔单药治疗将血压控制在<140/90 mmHg)有关人口统计学和孕妇血流动力学变量, 并进行logistic回归分析, 以建立预测将血压持续控制在上述水平的模型。孕妇接受定期检查直至分娩, 并在整个妊娠期间进行连续血流动力学监测。如果血压升高, 则再次采用预测模型决定是否需要增加其他抗高血压治疗(其他β受体阻滞剂或血管扩张剂)。 结果 : 根据连续血流动力学监测结果, 治疗使产前重度高血压发生率从18%降至3.8%。77%的孕妇服用β受体阻滞剂, 23%的孕妇服用血管扩张剂。β受体阻滞剂单药治疗血压控制良好组胎儿和孕妇的结局最好。该组就诊时以及整个妊娠期间血压较低, 心输出量维持较好, 胎儿生长受限发生率最低。需要两种药物联合治疗控制血压组血压持续较高, 胎儿生长受限发生率较高。就诊时或妊娠晚期由于外周血管阻力水平较高需要血管扩张剂治疗组, 其胎儿生长受限的发生率占所有病例的81%。 结论 : 妊娠期通过连续血流动力学监测指导高血压治疗, 能够明显降低重度高血压的发生率, 并能够鉴别高阻力、低输出量并伴有胎儿生长受限发生率升高的高血压孕妇。